Pemanfaatan Biografi Haji Ismail Mundu Sebagai Sumber Pembelajaran Sejarah Lokal di SMA Pelangi Nusantara - Sri Maharani; Andang Firmansyah; Edwin Mirzachaerulsyah (Journal on Education, 2024)
This study aims to explore information about the use of Haji Ismail Mundu's biography as a history lesson at SMA Pelangi Nusantara. The research method used is a qualitative method with a descriptive approach. Data collection techniques were collected through observation, interviews, and documentation. Then use the stages of data analysis in the form of data collection, data reduction, data presentation, verification / conclusion. The results showed the role of Hajj Ismail Mundu as Mufti, making it a forum for the public to ask questions about religious problems that came from various royal circles and from both the general public. Then there are three stages in the use of the biography of Haji Ismail Mundu, namely: the planning stage, the application stage and the Evaluation. The use of Haji Ismail Mundu's biography in its planning is adjusted to local historical material as well as the needs and understanding of the learners. Teachers use discussion and lecture methods. Before inviting students to discuss, the teacher provided material identifying the figure of Haji Ismail Mundu with the aim that students get an idea of the figure of Haji Ismail Mundu. The form of evaluation given to student participants is a description of the material presented. Based on the results of this study, several obstacles were found such as limited learning time on this local history material because it was not included in the basic competence content, the solution carried out by the teacher was to apply the group discussion method, this could save time so that all material could be studied.